Prospects for the use of sharing mechanisms in the tourism industry of Ukraine - Hanna Haponenko; Olena Yevtushenko; Irina Shamara; Valeriya Annenkova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
The sharing economy is constantly expanding its boundaries, offering not only traditional accommodation options, but also new forms, such as housing on wheels, tree houses and other unique objects. This opens up even more opportunities for travelers to experiment and create a memorable vacation. The sharing economy also leads to the expansion of the ecosystem of services offered to travelers. In addition to housing rentals, platforms are starting to offer various additional services, such as car rentals, organizing tours, ordering food, and much more. This creates a more convenient and integrated experience for travelers, allowing them to manage all aspects of their vacation from a single source. The purpose of the study is to analyze the impact of the sharing economy on the tourism industry, as well as to study the impact of the sharing model on the business environment in the field of tourism. To achieve the goal, the following tasks were set and solved in the work: the role of technologies and digital platforms in the development of sharing in tourism was investigated; the main mechanisms of the sharing economy in tourism are considered; the advantages and disadvantages of using sharing mechanisms in tourism are analyzed; the prospects for the application of sharing mechanisms in the tourism industry of Ukraine are highlighted. In the course of the research, general scientific approaches were used, such as logical analysis and comparison, as well as methods of summarizing and processing information using economic and statistical methods of analysis. Research results. One of the important ways of developing the sharing economy is the integration of the latest technologies, such as artificial intelligence and blockchain technology. Blockchain technology can increase the level of security and trust between landlords and tenants, providing transparency and reliability in transactions. Conclusions. Blockchain technology can contribute to the activation of the sharing economy, making it more accessible and efficient. For example, with the help of this technology, you can automate transactions, which will reduce costs and time for their implementation. Ultimately, this model of the economy can contribute to solving the problem of social inequality, which is very relevant today.